A Seven Bit Silicon Optical True Time Delay Line for Ka-Band Phased Array Antenna - Pengfei Zheng; Chenquan Wang; Xuemeng Xu; Jing Li; Dongdong Lin; Guohua Hu; Ruohu Zhang; Binfeng Yun; Yiping Cui (IEEE Photonics Journal, 2019)
A seven-bit optical true time delay unit with a delay tuning increment of 1.42 ps was designed and fabricated on silicon photonics platform, which can be utilized in Ka-band phased array antenna systems. The delay unit consists of eight thermo-optical switches and seven waveguide delay lines with different lengths. By manipulating the states of the thermo-optical switches, 128 stages of discrete time delays varying from 0 to 191.37 ps has been obtained with low average power consumption of 178.77 mW. Besides, the integrated delay unit was fabricated on the silicon-on-insulator chip that has a very compact footprint of 7.4 mm × 1.8 mm. In addition, as the waveguide delay dependence on the modulation frequency is very limited and can be neglected, the proposed delay unit should process a large bandwidth that allows it to be utilized in microwave applications with abundant bandwidth.